FDA approval summary: Dalteparin for the treatment of symptomatic venous thromboembolism in pediatric patients. Issue 12 (8th September 2020) - Merino, Margret; Richardson, Nicholas; Reaman, Gregory; Ande, Anusha; Zvada, Simbarashe; Liu, Chao; Hariharan, Sudharshan; De Claro, R. Angelo; Farrell, Ann; Pazdur, Richard
Abstract: On May 16, 2019, the U.S. Food and Drug Administration (FDA) approved dalteparin sodium for the treatment of symptomatic venous thromboembolism (VTE) to reduce the risk of recurrence in pediatric patients 1 month of age and older. Approval was primarily based on FDA review of a single‐arm trial evaluating dalteparin administered subcutaneous twice daily in 38 pediatric patients with symptomatic VTE. Efficacy was based on the achievement of therapeutic plasma anti‐Xa levels. The FDA concluded that dalteparin has efficacy and acceptable safety for pediatric patients.